A Study of Plasma Anti-Thyroperoxidase Antibodies and Anti-Thyroglobulin Antibodies in patients with Hypothyroidism - Umer Saeed, Saman Saeed, Qanita Mehmood, Asima Ayyub (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the plasma anti-thyroperoxidase antibodies (Anti-TPO) and anti-thyroglobulin antibodies (ATG) in hypothyroid patients Methods: This study was carried out at Arif Clinical Laboratory and Diagnostic center, Lahore. Samples were collected from 750 patients diagnosed with hypothyroidism. The blood samples were analyzed for the levels of anti-thyroperoxidase antibodies (n=450) and anti-thyroglobulin (n=300) antibodies. Depending upon the serum levels of these antibodies, the obtained titerswere categorized as normal, mildly elevated, moderately elevated and highly elevated. Duration of study was around08 months, extending from November 2021 to May 2022. Results: Among the total 750 patients with hypothyroidism, 450 were estimated for Anti-TPO antibodies, whereas, 400 patients were analyzed ATG antibodies. Anti-TPO antibodies were normal in 191 patients (42.44%) and high levels were observed in 259 patients (57.55%), indicating a greater role of these antibodies in the causation of hypothyroidism. In contrast, among the 300 patients analyzed for ATG antibodies, 213 patients had normal levels (71%), while 87 has high plasma levels of these antibodies (29%) Practical Implications: Current study provides an insight into the more frequent incidence of Anti-TPO antibodies, thus indicating its more crucial role in causing hypothyroidism in the given population. Therefore, estimation of these autoantibodies earlier in the disease can serve as better indicators of the severity and response to treatment, compared with Anti-TGB antibodies, which are present less frequently in patients with hypothyroidism Conclusion: Anti-TPO antibodies were found to be high in 57.55% patients (n=450) with hypothyroidism, indicating its greater role in the causation of hypothyroidism, whereas, ATG were high in only 29% patients (n=300). The results stress the need to evaluate all patients of hypothyroidism with plasma antibody levels for early diagnosis and a prompt management plan. Keywords: anti-thyroglobulin, anti-thyroperoxidase, hypothyroidism, Thyroxine, Triiodothyronine